2003
DOI: 10.7589/0090-3558-39.3.638
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Lead, Steel, and an Iron-Tungsten-Nickel Shot to Mallard Ducks (Anas Platyrhynchos)

Abstract: Twenty mallards (Anas platyrhynchos) of both sexes were dosed by oral gavage with Heavi-Shot (H-S; Environ-Metal, Inc., Sweet Home, Oregon, USA) pellets, 20 with steel shot, and 10 with lead (Pb) pellets, all of equal size. All pellets were fired from a shotgun into an absorbent material, retrieved, and weighed prior to introduction into the ducks. Birds were fed whole kernel corn and grit and observed for signs of toxicity for 30 days following dosing. HeviShot pellets lost an average of 6.2% of their mass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The nonretention of some lead shot in the gizzard is normal. Brewer et al (2003) reported elimination of 8.8% of shot between days 4 and 22 after ingestion. The gradual reduction of shot size observed in our study, until its complete degradation by around day 30, also is normal and in agreement with previous studies (Srebocan and Rattner, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The nonretention of some lead shot in the gizzard is normal. Brewer et al (2003) reported elimination of 8.8% of shot between days 4 and 22 after ingestion. The gradual reduction of shot size observed in our study, until its complete degradation by around day 30, also is normal and in agreement with previous studies (Srebocan and Rattner, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Shot pellets retained in the gizzard are ground by the abrasive action of grit and dissolved by the acid secretions of the proventriculus, with lead salts absorbed into the bloodstream (Mateo et al, 1997). The degree of metal erosion of individual shot in the mallard gizzard is directly correlated to the amount of metal that is available for uptake and circulation (Brewer et al, 2003). Differences in degradation can be related to varied diets used in experiments or other factors and should be considered when estimating prevalence of lead shot exposure based on gizzard examinations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily, these investigations have focused on the safety of implanted medical devices (International Agency for Research on Cancer [IARC], 1999) and the development of "nontoxic" hunting ammunition (Brewer, Fairbrother, Clark, & Amick, 2003;Kelly et al, 1998;Kraabel, Miller, Getzy, & Ringelman, 1996;Mitchell et al, 2001a;Mitchell et al, 2001b;Mitchell et al, 2001c). Little has been done throughout the years to assess the long-term health effects of military-relevant metals and metal mixtures (Kane, Kasper, & Kalinich, 2009).…”
Section: Health Effects Of Embedded Fragments: Animal Studiesmentioning
confidence: 98%